PEMANFAATAN SABUT KELAPA SEBAGAI CAMPURAN PEMBUATAN GENTENG BETON - Afkar, Minhajul; Adyputra, Alief Firjatullah; Putra Havia, Rafeiza Rizki Putra Havia Rizki; Yudaningrum, Farida (Universitas PGRI Semarang, 2025)
To create a comfortable residence in urban areas, innovation is needed in roof tile making materials to reduce the rate of solar heat absorbed by the roof tiles. Therefore, new innovations in concrete roof tiles so that concrete roof tiles can compete in the market, with a coconut fiber composition of 0%, 1%, 3%, 5%. The addition of coconut fiber fiber is expected to reduce the weight of concrete roof tiles which is the main problem by using less sand in the composition without reducing the bending load and water permeability (impermeability) of concrete roof tiles. It is also hoped that this innovation can reduce the use of tin roofs and choose concrete roofs. which is more environmentally friendly. After testing flexural strength, water seepage and water absorption, several results were obtained. Results from flexural strength testing, bending load characteristics at 1% variation; 3% and 5% yield 153 kg; 193.8 kg; and 214.2 kg. For testing water seepage or impermeability with the addition of 0% coconut fiber; 1%, 3% and 5% all have no water droplets dripping on the bottom surface of the roof tiles due to water seepage except for the 5% mixture which has water droplets underneath. And for water absorption or porosity of concrete roof tiles with the addition of 0% coconut fiber; 1%; 3%; and 5%, namely 11.1%; 11.3%; 11.3% and 14.7%. So it can be concluded that concrete roof tiles with a 3% coconut fiber mixture are the most ideal mixture, noting that the weight of the concrete roof tiles will increase when exposed to water because they still do not meet the SNI standards for water absorption (porosity).